Hubungan Shalat Dhuha dengan Kecerdasan Spiritual Siswa Kelas XII di SMA Negeri 2 Kota Bogor - Annisa Handayani; Chodidjah Makarim; Ikhwan Hamdani (As-Syar'i: Jurnal Bimbingan & Konseling Keluarga, 2022)
This research is based on the framework of thinking that worship is an effort to get closer to the creator. One of them is the Duha prayer, prayer can improve the quality of life of a Muslim because many things are educational in prayer. One of the benefits of dhuha prayer is that it can increase intelligence. spiritual intelligence is very necessary considering that spiritual intelligence is a necessary foundation for the effective functioning of intellectual intelligence (IQ) and emotional intelligence (EQ). The main purpose of this study was to determine the implementation of the Dhuha prayer program for Class XII students at SMA Negeri 2 Bogor City, namely 1) To determine the implementation of the Dhuha prayer program for Class XII students at SMA Negeri 2 Bogor City. 2) To determine the spiritual intelligence of Class XII students at SMA Negeri 2 Bogor City. 3) To find out whether there is a significant relationship between the Dhuha prayer program and the spiritual intelligence of Class XII students at SMA Negeri 2 Bogor City. The research method used is correlational quantitative method. The population of class XII totaling 331 students and the research sample as many as 80 students with a sampling technique using simple random sampling. The results of the study through the correlation test showed that there was a significant moderate relationship between PAI learning outcomes and emotional intelligence. This can be seen from the results of the correlation test for variables X and Y of 0.551. A positive rxy value indicates the direction of the two variables is positive. Keywords: Duha prayer program, spiritual intelligence, Islamic religious education